CORRELATION BETWEEN TIME TO POSITIVITY BLOOD CULTURE AND PROCALCITONIN ON BACTEREMIA PATIENT - Nelly Elfrida Samosir; Ricke Loesnihari; Adi Koesoema Aman (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2019)
Bacteremia causes a high mortality rate. Detection of bacteremia is needed as quickly as possible. The gold standard for bacteremia is blood culture which takes between 24-48 hours. Procalcitonin (PCT) is a marker of infection that is caused by bacteria that can be detected quickly in 2-6 hours. Time to positivity (TTP) blood culture is affected by the initial amount of bacteria and the addition of procalcitonin stimulated by bacteria that causes bacteremia where short TTP and high PCT show bad clinical conditions. Analytical cross sectional research on patients with bacteremia. Fourty-six bacteremia cases become the sample of research. Time to Positivity is calculated with Bactec 9050 and Procalcitonin is analyzed with mini VIDAS B.R.A.H.M.S. Examination is conducted in Department of Clinical Pathology FK-USU/ Installation of Clinical Pathology of RSUP H. Adam Malik, Medan, June – October 2016. There was significant correlation between Time to Positivity blood culture and procalcitonin on bacteremia patients (p<0.05). There was no significant correlation between Time to Positivity and procalcitonin on bacteremia which was caused by gram-positive bacteria or Gram-negative bacteria (p>0.05). Procalcitonin was significantly higher on bacteremia, which was caused by Gram-negative bacteria compared to Gram-positive bacteria (p<0.05). There was significant correlation between Time to Positivity blood culture and procalcitonin on bacteremia patients. Significantly higher levels of procalcitonin in cases of bacteremia are more likely to be caused by Gram-negative bacteria than Gram-positive bacteria.